저산소 조건에서 항생제들이 인간 간암 세포의 생존에 미치는 영향 - 이영택(Young Tag Lee); 한미정(Mee-Jung Han); 임선하(Sun Ha Lim); 박성환(Sung Hwan Park); 서헌석(Hun Suk Suh); 박재복(Jae Bok Park); 김양일(Yang Il Kim); 이종원(Jongwon Lee) (Annals of surgical treatment and research, 2006)
Purpose: Antibiotics that kill or suppress the growth of bacteria also affect tumors directly or indirectly. The authors aimed to show whether some antibiotics can improve cancer cell survival under hypoxic conditions, and how the antibiotics improve the cells under hypoxic conditions. Methods: Human hepatocellular carcinoma cells (HepG2) were grown at 1% oxygen concentration. Cell numbers, glucose concentrations and lactic acid concentrations in the medium were measured at different incubation times, in the absence or presence of aminoglycosides, tetracyclines, quinolones, penicillins, cephalosporins, sulfonamides, or chloramphenicols. DNA fragmentation assay was performed to study the mechanism how some antibiotics improve the cell survival under hypoxic conditions. Results: Of the antibiotics tested, only aminoglycosides, tetracyclines, quinolones and the chloramphenicol improved cell survival under hypoxic conditions. Geneticin (G418), an aminoglycoside chosen as an example, improved cell survival even if glucose in the medium was completely consumed. At the same time, the appearance of DNA ladder was delayed in the presence of geneticin, which was also the same for the other antibiotics that improved cell survival under hypoxic conditions. Conclusion: Some antibiotics improved hepatocellular carcinoma cells under ischemic conditions by inhibiting apoptosis. The results implies that the antibiotics might adversely affect solid tumors, by improving cancer cell growth where hypoxic or ischemic conditions occur in the core region. Therefore, we might be cautious in choosing antibiotics for cancer patients with solid tumors, especially when the patients should be treated with antibiotics for a long time. (J Korean Surg Soc 2006;71:31-38) KCI Citation Count: 4